MANIEA: a microbial association network inference method based on improved Eclat association rule mining algorithm - Liu, Maidi; Ye, Yanqing; Jiang, Jiang; Yang, Kewei (Bioinformatics (Oxford, England), 2021)
Abstract Motivation Modeling microbiome systems as complex networks are known as the problem of network inference. Microbial association network inference is of great significance in applications on clinical diagnosis, disease treatment, pathological analysis, etc. However, most current network inference methods focus on mining strong pairwise associations between microorganisms, which is defective in reflecting the comprehensive interactive patterns participated by multiple microorganisms. It is also possible that the microorganisms involved in the generated network are not dominant in the microbiome due to the mere focus on the strength of pairwise associations. Some scholars tried to mine comprehensive microbial associations by association rule mining methods, but the adopted algorithms are relatively basic and have severe limitations such as low calculation efficiency, lacking the ability of mining negative correlations and high redundancy in results, making it difficult to mine high-quality microbial association rules and accurately infer microbial association networks. Results We proposed a microbial association network inference method ‘MANIEA’ based on the improved Eclat algorithm for mining positive and negative microbial association rules. We also proposed a new method for transforming association rules into microbial association networks, which can effectively demonstrate the co-occurrence and causal correlations in association rules. An experiment was conducted on three authentic microbial abundance datasets to compare the ‘MANIEA’ with currently popular network inference methods, which demonstrated that the proposed ‘MANIEA’ show advantages in aspects of correlation forms, computation efficiency, adjustability and network characteristics. Availability and implementation The algorithms and data are available at: https://github.com/MaidiL/MANIEA.